HUBUNGAN ANTARA FEAR OF FALLING DENGAN AKTIVITAS FISIK PADA LANSIA DI PANTI JOMPO HAJJAH ANDI HASMAH NOOR - Inez Deviantika (2023)
Background: In elderly, physical changes can affect the process of physical activity. One of the factors that affect the inhibition of physical activity is the fear of falling. The fear of falling arises from the experience felt by the elderly, they will avoid activities that pose a risk of falling for themselves. In another study conducted over 155 elderly, 77 elderly (49.7%) were found to have a high level of fear of falling and 102 elderly (65.8%) had a high risk of falling. Based on the explanations that have been presented, the authors are interested in researchs "The Relationship between Physical Activity and Fear of Falling inelderly at hajjah andi hasmah noor nursing home". Purpose: the aim of this study was to determine the relationship between physical activity and fear of falling in elderly. Method: The research method used is cross sectional with correlative approach. The paramater used the Physical Activities Scale For Elderly (PASE-I) and Modified Falls Efficacy Indonesian Scale (FES-I) measuring instruments. Results: Based on the results of a study of 30 elderly, 14 elderly (46.7%) experienced high anxiety about falling. The acquisition of the Chi-Square correlation test value showed p = 0,03 or p=0,05 so that the relationship between the two variables, namely fear of falling and physical activity, was significant. Conclusion: In this study, there was a significance relationship between fear of falling and physical activity in the elderly at the hajjah andi hasmah noor nursing home. Keywords: physical activity; fear of falling; elderly; risk of falling